Dissociation in response to methylphenidate on response variability in a group of medication naïve children with ADHD - JOHNSON, KATHERINE; ROBERTSON, IAN; GILL, MICHAEL; DAIBHIS, AOIFE; DALY, MICHAEL; FITZGERALD, MICHAEL (My University, 2008)
Increased variability in reaction time (RT) has been proposed as a cardinal feature of attention deficit hyperactivity disorder (ADHD). Increased variability during sustained attention tasks may reflect inefficient fronto-striatal and fronto-parietal circuitry; activity within these circuits is modulated by the catecholamines. A disruption to dopamine signaling is suggested in ADHD that may be ameliorated by methylphenidate (MPH). This study investigated the effects of MPH administration on the variability in RT and error performance on a sustained attention task of a group of 31 medication naive children with ADHD, compared with 22 non-ADHD, non-medicated, control children. All children performed the fixed-sequence sustained attention to response task (SART) at two time-points: at baseline and after six weeks. The children with ADHD were tested when medication naive at baseline and after six weeks of treatment with MPH and whilst on medication. The medication naive children with ADHD performed the SART with greater errors of commission and omission when compared with the control group. They demonstrated greater standard deviation of RT and fast moment-to-moment variability. They did not differ significantly from the control group in terms of slow variability in RT. MPH administration resulted in reduced and normalised levels of commission errors and fast, moment-to-moment variability in RT. MPH did not affect the rate of omission errors, standard deviation of RT or slow frequency variability in RT. MPH administration may have a specific effect on those performance components that reflect sustained attention and top?down control rather than arousal.
PUBLISHED
(243) PMID 18289615 ABSTRACT: Increased variability in reaction time (RT) has been proposed as a cardinal feature of attention deficit hyperactivity disorder (ADHD). Increased variability during sustained attention tasks may reflect inefficient fronto-striatal and fronto-parietal circuitry; activity within these circuits is modulated by the catecholamines. A disruption to dopamine signaling is suggested in ADHD that may be ameliorated by methylphenidate (MPH). This study investigated the effects of MPH administration on the variability in RT and error performance on a sustained attention task of a group of 31 medication naïve children with ADHD, compared with 22 non-ADHD, non-medicated, control children. All children performed the fixed-sequence sustained attention to response task (SART) at two time-points: at baseline and after six weeks. The children with ADHD were tested when medication naive at baseline and after six weeks of treatment with MPH and whilst on medication. The medication naïve children with ADHD performed the SART with greater errors of commission and omission when compared with the control group. They demonstrated greater standard deviation of RT and fast moment-to-moment variability. They did not differ significantly from the control group in terms of slow variability in RT. MPH administration resulted in reduced and normalised levels of commission errors and fast, moment-to-moment variability in RT. MPH did not affect the rate of omission errors, standard deviation of RT or slow frequency variability in RT. MPH administration may have a specific effect on those performance components that reflect sustained attention and top-down control rather than arousal.
Keywords: Response time; Methylphenidate; Attention Deficit Hyperactivity Disorder; ADHD; Variability; Dopamine; Neuroscience; ADD/ADHD; ADD/ADHD; ADHD; ADHD; ADHD Lifetime Impairment Survey; ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD); Adolescent Psychiatry; Attention Deficit Hyperactivity Disorder (ADHD); CHILD PSYCHIATRY; COMMUNITY PSYCHIATRY; CONSULTATION LIAISON PSYCHIATRY; CONSULTATION-LIAISON PSYCHIATRY; DISORDER ADHD; GENERAL HOSPITAL PSYCHIATRY; LIAISON PSYCHIATRY; METHYLPHENIDATE; Neuropsychiatry; Neuropsychiatry; PSYCHIATRY; Psychiatry; Psychiatry; TRAINEES IN PSYCHIATRY; adult ADHD; child and adolescent Psychiatry; neurodevelopmental psychiatry